Will innovation be the true game-changer of food systems transformation? - Alliance of Bioversity International and CIAT (CGIAR System Organization, 2022)
How innovations, which have been recognized to contribute to the current resource-intensive, wasteful and fossil fuel-based paradigm of mass production and mass consumption which we live in and feed from, could, suddenly become the solution that leads us to food system sustainability?